Appendix Tumours in Emergency Abdominal Surgery - A. V. Melnikova; A. I. Sendik; A. G. Hasanov (Креативная хирургия и онкология)
Introduction. Tumour neoplasms of the appendix represent a rare pathology with a frequency of up to 0.1 % and 0.5 % of all performed appendectomies and all forms of malignant tumours of the colon, respectively. Due to the lack of specific diagnosis and asymptomatic development of the disease, such neoplasms are diagnosed accidentally during an emergency operation for acute appendicitis or according to the results of a morphological study of postoperative material.Materials and methods. A retrospective analysis of appendix neoplasm cases was performed in patients hospitalised in the surgical departments of City Clinical Hospital No. 8 in 2006-2016. A total of 3298 surgical interventions for acute appendicitis were carried out for this period in the patients aged from 18 to 86 years.Results. Upon admission, all patients had a clinical status of appendicitis. In 3 cases, preoperative ultrasound revealed an expansion of the intestinal loops, pneumatosis and local fluid accumulation. In the setting of mucocele, the sonogram revealed a 70x48 mm ovoid thin-walled liquid formation with smooth contours and peripheral blood flow. In the remaining patients, no pathological changes were detected by ultrasound.Discussion. According to the results of histological examination, 6 carcinoid tumours were diagnosed in 5 men and 1 woman aged 38-62 years (0.18 %). The appendix adenocarcinoma was diagnosed in 2 women and 1 man aged 7681 years (0.09 %). One case of an appendix mucinous tumour in a 67-year-old woman was established intraoperatively (0.03 %). The appendix neoplasm frequency comprised 0.3 % of all appendectomies performed.Conclusions. The conducted analysis showed that, even with the possibility of the comprehensive examination of patients, the diagnosis of tumour diseases of the appendix in emergency surgical care remains to problematic.